Assessment of the nature of interactions of cations with cycloheptatriene derivatives using change in the aromaticity: Comparison with electron density and NBO results. (17th April 2020) - Valadbeigi, Younes; Gal, Jean-François
ABSTRACT: Interactions of cycloheptatriene derivatives, C7 H6 X, (X = NH, PH, AsH, O, S, Se) with the cations H +, CH3 +, Cu +, Al +, Li +, Na +, and K + are studied using B3LYP functional and 6-311++G(d, p) basis set. The calculated gas-phase cation affinities (CA) and cation basicities (CB) for all molecules decrease as H + > CH3 + > Cu + > Al + > Li + > Na + > K + . We used the induced aromaticity in the 7-membered ring of C7 H6 X upon interaction with the cations, M +, as a measure of C7 H6 X/M + interaction. Nucleus-independent chemical shift (NICS) and harmonic oscillator model of aromaticity (HOMA) were used as two indices of aromaticity. The highest and lowest induced aromaticities were observed for interactions of H + and K +, respectively. Also, the aromaticity induced by interaction with a cation in C7 H6 AsH and C7 H6 PH was larger than that in C7 H6 NH and C7 H6 O. Hence, the aromaticity was considered as a measure of covalency for the C7 H6 X/M + interactions showing a rational dependence on both the molecule and cation. The nature of the interactions was also assessed using electron density, charge distribution analysis and NBO calculations. The results of the aromaticity indices, NICS and HOMA, were compared with the electron density and NBO results. GRAPHICAL ABSTRACT: